The Landscape of Accounting Related Research in Indonesia: Mapping Distinctive Settings and Future Research Agenda - Kristanto, Ari Budi; Cao, June (Elsevier, 2024)
Purpose – This systematic literature review presents the evolution of accounting-related research in the Indonesian context. We examine 55 academic articles from the initial 296 records of accounting and finance research in the Q1 Scopus-indexed journals from 1995 to 2022. This study sheds light on Indonesia’s main research streams, unique settings and urgent future research agenda. Design/methodology/approach – This study adopts a systematic approach for a comprehensive literature review. We select articles according to a series of criteria and compile the metadata for the bibliographic mapping. Findings – Our bibliometric analysis suggests five main research streams, namely (1) political connection, (2) capital market, (3) audit and accountability, (4) firm policy and (5) banking.We identify the following distinctive country settings, which are well discussed in extant literature: political connection, two-tier board system, weak accounting profession, information opacity and cultural impact on accounting. We outline prospective agendas to examine the institutional mechanisms’role in addressing major environmental challenges through accountability. Originality/value – This study offers unique contributions to the literature by comprehensively reviewing accounting-related research in Indonesia. Despite Indonesia’s economic and environmental importance, it has received limited attention from scholars. Using dynamic topic analysis, we highlight the need to examine the role of informal institutions, such as political connections and culture and formal institutional mechanisms, such as corporate governance and environmental disclosure